2018
DOI: 10.3389/fnmol.2018.00098
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Betulinic Acid on LPS-Induced Neuroinflammation Involve M2 Microglial Polarization via CaMKKβ-Dependent AMPK Activation

Abstract: In response to the microenvironment, microglia may polarize into either an M1 pro-inflammatory phenotype, exacerbating neurotoxicity, or an M2 anti-inflammatory phenotype, conferring neuroprotection. Betulinic acid (BA) is a naturally pentacyclic triterpenoid with considerable anti-inflammatory properties. Here, we aim to investigate the potential effects of BA on microglial phenotype polarization and to reveal the underlying mechanisms of action. First, we confirmed that BA promoted M2 polarization and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 50 publications
2
43
0
1
Order By: Relevance
“…In this context, promoting an M1-M2 switch could be an interesting approach to attenuate inflammation of the neural tissue ( Hu et al, 2015 ; Xu et al, 2015 ). In line, a recent study showed that betulinic acid (BA), a naturally pentacyclic triterpenoid with anti-inflammatory properties, promotes M2 polarization and inhibits M1 polarization in LPS-stimulated BV2 microglial cells and in the cerebral cortex of LPS-injected mice through calmodulin-dependent protein kinase kinase β (CaMKKβ)-dependent AMP-activated protein kinase (AMPK) activation ( Li et al, 2018 ). In another study, Xu et al (2015) showed that telmisartan, a potent angiotensin II receptor blocker, also prevents LPS-induced microglia activation throughout M2 microglia polarization through CaMKKβ-dependent AMPK activation.…”
Section: Microglia Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, promoting an M1-M2 switch could be an interesting approach to attenuate inflammation of the neural tissue ( Hu et al, 2015 ; Xu et al, 2015 ). In line, a recent study showed that betulinic acid (BA), a naturally pentacyclic triterpenoid with anti-inflammatory properties, promotes M2 polarization and inhibits M1 polarization in LPS-stimulated BV2 microglial cells and in the cerebral cortex of LPS-injected mice through calmodulin-dependent protein kinase kinase β (CaMKKβ)-dependent AMP-activated protein kinase (AMPK) activation ( Li et al, 2018 ). In another study, Xu et al (2015) showed that telmisartan, a potent angiotensin II receptor blocker, also prevents LPS-induced microglia activation throughout M2 microglia polarization through CaMKKβ-dependent AMPK activation.…”
Section: Microglia Polarizationmentioning
confidence: 99%
“…Microglial cells express triggering receptor of myeloid cell-2 (TREM2), which is an important negative regulator of NF-κB. In vitro studies showed that TREM2 overexpression inhibits neuroinflammation by down-regulating PI3K/AKT and NF-κB signaling in BV2 microglia ( Zhong et al, 2017 ; Li et al, 2018 ). Curiously, LPS downregulates the expression of TREM2 through the activation of JNK and NF-κB signaling pathways, resulting in a pro-inflammatory vicious cycle ( Zhong et al, 2017 ).…”
Section: Intracellular Signaling Targets For Reducing Microglia Inflamentioning
confidence: 99%
“…Interestingly, it has also been shown to promote M2 anti-inflammatory phenotype polarization of lipopolysaccharide (LPS)-stimulated BV-2 microglial cells and to inhibit M1 proinflammatory phenotype. This study was carried out via calmodulin-dependent protein kinase β (CaMKKβ)-dependent AMPK activation, which was further confirmed in mice brains treated with betulinic acid [127].…”
Section: Betulinic Acidmentioning
confidence: 69%
“…Accumulating data from experiments using LPS as a trigger for pro‐inflammatory reactions indicate that AMPK activation induces a microglial phenotypic shift from pro‐inflammatory to anti‐inflammatory in AMPK activation‐dependent manner. In primary cultured microglia or BV2, LPS‐induced pro‐inflammatory reaction is associated with reduction in phospho (p)‐AMPK (activated AMP) (Li et al, 2018b; Park et al, 2018; Xu et al, 2015; Zhou et al, 2014), and AMPK activators including metformin and 5‐aminoimidazole‐4‐carboxamide 1‐β‐D‐ribofuranoside (AICAR) suppress pro‐inflammatory and enhance anti‐inflammatory reactions (Giri et al, 2004; Lee et al, 2015; Lu et al, 2010; Li et al, 2018a; Xu et al, 2015; Park et al, 2018; Wang et al, 2018d; Zhou et al, 2014; Velagapudi et al, 2017; Chen et al, 2014). For example, AICAR (an analogue of AMP) attenuates LPS‐induced activation of NF‐κB and inhibits expression of proinflammatory cytokines (TNF‐α, IL1β, IL‐6) and iNOS, and these effects of AICAR are inhibited by the dominant negative form of AMPK and anti‐sense AMPK treatment in primary rat astrocytes, microglia, and peritoneal macrophages (Giri et al, 2004).…”
Section: Ampk As a Regulator Of Inflammationmentioning
confidence: 99%
“…For example, AICAR (an analogue of AMP) attenuates LPS‐induced activation of NF‐κB and inhibits expression of proinflammatory cytokines (TNF‐α, IL1β, IL‐6) and iNOS, and these effects of AICAR are inhibited by the dominant negative form of AMPK and anti‐sense AMPK treatment in primary rat astrocytes, microglia, and peritoneal macrophages (Giri et al, 2004). Betulinic acid (BA), a naturally occurring pentacyclic triterpenoid, attenuates LPS‐induced pro‐inflammation reaction in BV‐2 microglial cells via CaMKKβ‐dependent AMPK activation, and compound C (an AMPK inhibitor) and AMPK siRNA abolish the effects, although BA does not affect phagocytic activation induced by LPS (Li et al, 2018a). ENERGI‐F704, an AMPK agonist, decreases the protein level and nuclear translocation of NF‐κB, leading to reduction of pro‐inflammatory mediators, such as IL‐6, TNF‐α, iNOs, and COX‐3 in LPS‐stimulated microglia (BV2) (Chen et al, 2014).…”
Section: Ampk As a Regulator Of Inflammationmentioning
confidence: 99%